Cultivating Secondary Students’ Speaking Skill Using Tea Party Technique - Joe Kevin; Rahma Dianti; Gaya Tridinanti (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
The study focused on using the Tea Party Technique to improve the speaking abilities of eighth-grade students. The Tea Party technique is a cooperative strategy that encourages the students to actively communicate with their speaking partners. The purpose of the study was to examine the effectiveness of the Tea Party technique in improving the speaking abilities of eighth-grade students and to ascertain whether there was a difference in the speaking abilities between the students who received a treatment using the Tea Party technique and those who did not. A quasi-experimental design was employed by the researchers. The eighth-grade students of SMP Tri Dharma Palembang in the 2020–2021 academic year were involved as the target population. The researchers used cluster random sampling to choose the sample. 42 students participated as the sample, which was split into an experimental and a control group. Every group had twenty-one participants. An oral test was used to gather the data. The test was administered twice. Both the Paired Sample T-Test and the Independent Sample T-Test were used to analyze the gathered data. The results of the Paired Sample T-Test showed that the Tea Party technique was effective in improving the eighth-grade students' speaking skills. The Independent Sample T-Test also showed that there was a significant difference in the students' speaking skills between those who were taught using the Tea Party Technique and those who were not.